1979
DOI: 10.2307/468762
|View full text |Cite
|
Sign up to set email alerts
|

Mervelous Signals: Poetics, Sign Theory, and Politics in Chaucer's Troilus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The Johns Hopkins University Press is collaborating with JSTOR to digitize, preserve and extend access to New Literary History. in forme of speche is chaunge ... Troilus and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…2. Translatio studü et imperil has been studied from various perspectives; e.g., historical (Curtius 1973: 27-30), linguistic (Vance 1979), and literary (Freeman 1979). 3.…”
Section: Notesmentioning
confidence: 99%
“…2. Translatio studü et imperil has been studied from various perspectives; e.g., historical (Curtius 1973: 27-30), linguistic (Vance 1979), and literary (Freeman 1979). 3.…”
Section: Notesmentioning
confidence: 99%
“…As such, it takes its place in a growing body of research that has revealed, recently, how well Chaucer's literary texts illustrate the awareness of sign theory in medieval culture both within and apart from the scholastic tradition (e.g., Vance 1979;Irvine 1985). Stock shows how, ranging from self-conscious usage of the term 'signe' to the nonverbal physical gestures of the tale's characters, Chaucer's attention to semiotic phenomena is further developed in this text through artistic usage of verbs of facture or creation -Brought to you by | University of Queensland -UQ Libr Authenticated Download Date | 6/23/15 11:08 AM such terms as, in Middle English, maken, schapen, and impressen -which function subtextually to reinforce the characters' reenactment of the Fall.…”
Section: Introductionmentioning
confidence: 99%